2016
DOI: 10.1080/10502556.2016.1150189
|View full text |Cite
|
Sign up to set email alerts
|

Not Even Cold in Her Grave: How Postbereavement Remarried Couples Perceive Family Acceptance

Abstract: Following the interviews of 24 participants concerning the death of their spouse and subsequent remarriage, a pattern of unsolicited responses concerning perceived acceptance of family emerged. Through grounded theory qualitative analysis, a continuum of acceptance was developed ranging from welcoming acceptance to active disapproval. Themes that influenced the perceived level of acceptance were (a) the length of time between death and courtship; (b) the length of the courtship itself; and (c) the level of fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Rather than moving through a similar pattern of grief in a predictable way, participants described these five experiences in different ways and at different times, creating more of a circular experience of loss. The research we found in our literature review confirmed a number of the individual experiences we found: for example, childrens’ feelings of losing one parent in body and then another in relationship (Anderson & Greene, 2013; Riches & Dawson, 2000), and family members simultaneously wanting to hold onto memories and let go as new relationships emerged (Engblom-Deglmann & Brimhall, 2016; Simhi-Meidani & Koren, 2018). However, the shared relational experiences between adult children and their fathers - different experiences of loss in the same family, fathers looking back with unexpressed regret, and experiences of repair - were new to us.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Rather than moving through a similar pattern of grief in a predictable way, participants described these five experiences in different ways and at different times, creating more of a circular experience of loss. The research we found in our literature review confirmed a number of the individual experiences we found: for example, childrens’ feelings of losing one parent in body and then another in relationship (Anderson & Greene, 2013; Riches & Dawson, 2000), and family members simultaneously wanting to hold onto memories and let go as new relationships emerged (Engblom-Deglmann & Brimhall, 2016; Simhi-Meidani & Koren, 2018). However, the shared relational experiences between adult children and their fathers - different experiences of loss in the same family, fathers looking back with unexpressed regret, and experiences of repair - were new to us.…”
Section: Resultssupporting
confidence: 78%
“…Rather than trying to explain in a linear way why a person chooses to remarry after the loss of a long-term partner, we find it more helpful to look at the complex web of interrelating factors that impact decision-making. For many parents, the primary concern in remarrying someone new is that children (including adult children) will accept the new partner into the family (Engblom-Deglmann & Brimhall, 2016). Participants in a number of studies across several decades have identified wanting support from their families as their primary concern during this time (Lee et al, 2001; O’Neill & Keane, 2005; Visher & Visher, 1996).…”
Section: Reasons For Remarriagementioning
confidence: 99%
See 2 more Smart Citations